A A Respiratory Review on Covid-19: Pathophysiology, Diagnosis, Treatment, and Prevention - Thapa, Shankar; Nargund, Shachindra L.; Biradar, Mahalakshmi Suresha; Yadav, Suraj; Kumar Mishra, Bikesh (Journal of Biomedical and Pharmaceutical Research, 2022)
Coronavirus Disease-2019 (Covid-19), a global threat, is a viral-born disease affecting the respiratory tract and causing breathing problems. Due to its high spread nature, it spread through the world in a short period and is a declared global threat. The reported cases are slowing down now but the fight against covid-19 is still ongoing. Most people with covid-19 experience uncomplicated symptoms although it has created fatal fear in the world population. Still, most people from developing countries lack information and are in psychological distress. This review has explained the symptom, disease process, diagnostic measures, treatment schedule, and preventive measures of covid-19. Keywords: Coronavirus, Covid-19, respiratory disease, global threat